Prediction of electric motor performance by in-line testing of permanent excited rotors - Abersfelder, Sandra; Meyer, Alexander Wilhelm; Heyder, Andreas; Thanner, Marius; Franke, Jörg (2016 6th International Electric Drives Production Conference, EDPC 2016 - Proceedings, 2016)
The market growth of electric drives is pushed forward due to high coercive magnet material and new, more efficient motor designs. These new designs require only small tolerances within the whole manufacturing process. While quality assurance is well established within the stator manufacturing process, the rotor assembly process suffers from lack of testing. Hence, this gap causes rejects not detected until the end-of-line-test of the whole motor, measuring especially the back electromotive force (BEMF) and the total harmonic distortion (THD) of the output signal. To avoid rejects of whole motors at the end of the value chain, this paper presents the possibilities delivered by in-line magnetic field measuring of the rotor. Therefore, different testing methods, such as a commercial available monolithic hall array and a discrete hall line array are used and evaluated. Out of these measurement series a rotor KPI is defined in order to evaluate the rotor quality right after the measurement.
CRIS-Team Scopus Importer:2023-03-07
Keywords: BEMF; hall measurement; manufacturing tollerances; permanent magnet; synchronous motor